An Analysis on EFL Learners’ Perspectives of Online Learning during Covid-19 Pandemic - Siti Maysuroh; Laila Wati; Astrid Dwimaulani; Nurul Yusri; Siti Zurriyatun Sholihah (Jurnal Pedagogy, 2022)
The aim of this research is to investigate EFL students’ perspectives on the utilization of online learning during the COVID-19 pandemic. A survey method was applied. This research involves 40 students of the second, fourth, and sixth semesters of the English Study Program of a private University in Hamzanwadi for the academic year 2020-2021 as the participants. To collect the data, a questionnaire was administered via Google Forms. The data collected were then analyzed using a percentage formula. The results of the study indicate that most of the students believe that online learning has not provided a better experience dan results in improving their competencies. However, they agreed that it provides ease in their learning. In addition, based on the result of questionnaires, more than 50% of the students prefer direct-classroom learning to online learning and only resettled with online learning during the COVID-19 pandemic. In a nutshell, despite the COVID-19 pandemic, students still choose direct classroom learning.